Improving Quality of Life of the Elderly Hypertension with a Family Empowerment Approach: A Quasi-Experimental Method Study - Yuda, Hendri Tamara; Rahim, Syed Sharizman Bin Syed Abdul; Madrim, Mohd Faizal (South Eastern European Journal of Public Health, 2024)
Introduction: Elderly with hypertension not only face risks to their physical health but also often experience far-reaching impacts on psychological and social aspects that can lower their overall quality of life. Active family involvement is needed in the care of the elderly, so that the health of the elderly can be more optimal Objectives: This study explored the influence of family empowerment on the quality of life of the elderly with hypertension. Methods: A quantitative approach aimed at exploring the influence of family empowerment on the quality of life of the elderly with hypertension. The design used in this study is quasi-experiment with one group pre-test-post test. The study Population focuses on elderly with hypertension in Indonesia within the age range of 60-90 years. The number of samples of 56 respondents was selected by purposive sampling. Data collection took place before and after one month of families caring for the elderly with hypertension were given family empowerment. The instruments used are Quality of Life, which is measured by the Older People Quality Of Life (OPQOL-Brief). Data analysis was conducted using the Wilcoxon test in S.P.S.S. software version 27 Results: The statistical results show that Z is calculated as -4,889 and sig is 0.000, so it can be concluded that there is a difference in quality of life before and after family empowerment. Conclusions: The study confirms a difference in the quality of life for older adults with hypertension before and after being given family empowerment